Multicenter Phase I Study of Triapine in Combination with [177Lu]Lutetium-Dotatate in Patients with Well-Differentiated Neuroendocrine Tumors (ETCTN 10388) - Aman Chauhan; Heidi L. Weiss; Charles Kunos; Rani Jayswal; Bhavana Konda; Heloisa P. Soares; Daneng Li; Thorvardur R. Halfdanarson; Mary F. Mulcahy; Heather A. Jacene; Aman Khurana; Rakhi Modak; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: The next generation of theranostics studies is looking at novel combinations with radiation sensitizers to enhance peptide receptor radionuclide therapy’s efficacy. In this study, we present safety and efficacy data from a multicenter phase I study of a [177Lu]lutetium-dotatate–triapine combination in patients with gastroenteropancreatic (GEP) neuroendocrine tumors (NET). Patients and Methods: The study consisted of 2 phases (part A: dose escalation; part B: dose expansion) administering the recommended phase II doses (RP2D) for the 2 agents. All patients received 200 mCi of [177Lu]lutetium-dotatate on day 1 of four 8-week cycles, in combination with oral triapine administered at assigned dose levels (100, 150, or 200 mg) from day 1 to day 14 of each cycle. Results: A total of 31 (A: 15; B: 16) patients received treatment. Across the study, 9 patients experienced dose-limiting toxicities: grade 3 anemia (n = 1), grade 5 cardiac arrest (unrelated to investigational product; n = 1), and grade 4 neutropenia (n = 7). Based on the overall safety and pharmacokinetics data, a [177Lu]lutetium-dotatate (200 mCi) plus triapine (150 mg) dose was selected as the RP2D for the expansion phase. Grade ≥3 treatment-related adverse events were observed in 77% of patients: anemia (23%), nausea and vomiting (3%), lymphopenia (58%), neutropenia (35%), and decreased white blood cell count (39%). The majority of cytopenias were transient and resolved within 2 weeks. Among the 28 evaluable patients, the objective response rate was 21.4%, and the median progression-free survival has not been reached (median follow-up period, 23.7 months). Conclusions: The combination of [177Lu]lutetium-dotatate (200 mCi) and oral triapine (150 mg D1-14) was well tolerated and demonstrated preliminary activity in patients with well-differentiated GEP-NET (NCT04234568).